FLOOD RISK ANALYSIS DUE TO DAM BREAK AT BILI-BILI DAM, GOWA REGENCY, SOUTH SULAWESI BASED ON HEC-RAS MATHEMATICAL MODELING - Agusman
This research is to analyze the risk of flooding due to the collapse of the Bili-bili Dam with the aim of predicting the impacts when it occurs, as well as providing recommendations to reduce the risk. The method used is modeling using HEC-HMS for routing dam collapse discharge and HEC-RAS to model the accumulation that forms. The results obtained are a risk index map where there are 11 sub-districts in Makassar City, 9 sub-districts in Gowa Regency, 2 sub-districts in Takalar Regency, and 1 sub-district in Maros Regency. Based on the results of the risk index analysis submitted to the 2012 BNPB Perka, it was found that 1 sub-district was included in the low risk index category, 21 sub-districts were included in the medium risk index category, 1 sub-district was included in the high risk index category.